Patterns of growth dominance and neighborhood effects in eucalyptus plantations and tropical forests - Bui, Doi The, author; Binkley, Dan, advisor; Stohlgren, Thomas J., committee member; Steingraeber, David, committee member; Ryan, Michael G., committee member (Colorado State University. Libraries, 2008)
Forest stands have a broad range of tree sizes, even when all trees develop as a single cohort. Differences in size might result from different rates of resource uptake or resource use efficiency. Dominant trees often account for the majority of increment, but non-dominant trees can contribute a major part of stand growth in some cases. Pattern of growth dominance may provide predictive insight into the growth of trees and forest. My dissertation contains three chapters to explore growth dominance patterns of Eucalyptus plantations in Hawaii and Brazil, and natural tropical forests in Panama.
Department Head: Michael J. Manfredo.